The Effect of Interactive Multimedia on Students’ Cognitive Learning Outcomes on System Materials - Asysyura, Fajriani; Adnan, Adnan; Faisal, Faisal (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2023)
This study aimed to determine the influence of interactive multimedia on students' cognitive learning outcomes in class XI. This study employed a quasi-experimental method using Posttest-Only Control Design. The population is students of class XI MIPA. Samples were taken by random sampling; an experimental class that uses interactive multimedia with as many as 30 students and a control class that does not use interactive multimedia with as many as 30 students. The data collection technique is carried out by providing a post-test to obtain data on student cognitive learning outcomes, and the data analysis technique used is an independent sample t-test with a significant level (α) = 5%. Based on data analysis and hypothesis testing, it shows that there is an influence of interactive learning multimedia on cognitive learning outcomes because of the significant value of 0.000 < 0.05. There are differences in student results, which can be seen through hypothesis tests that H0 is rejected and Hi is accepted. Students accept the use of interactive multimedia in the classroom in carrying out the teaching and learning process. Based on the study results, it was concluded that interactive learning multimedia influences the cognitive learning outcomes of class XI students.